Solving A Special Quartic | x^4 - 12x =17

preview_player
Показать описание
🤩 Hello everyone, I'm very excited to bring you a new channel (aplusbi)
Enjoy...and thank you for your support!!! 🧡🥰🎉🥳🧡

When you purchase something from here, I will make a small percentage of commission that helps me continue making videos for you.
If you are preparing for Math Competitions and Math Olympiads, then this is the page for you!
You can find ARML books and many others here. CHECK IT OUT!!! ❤️ ❤️ ❤️

❤️ Thanks to @NadiehFan for one of the methods!

If you need to post a picture of your solution or idea:
#radicals #radicalequations #algebra #calculus #differentialequations #polynomials #prealgebra #polynomialequations #numbertheory #diophantineequations #comparingnumbers #trigonometry #trigonometricequations #complexnumbers #math #mathcompetition #olympiad #matholympiad #mathematics #sybermath #aplusbi #shortsofsyber #iit #iitjee #iitjeepreparation #iitjeemaths #exponentialequations #exponents #exponential #exponent #systemsofequations #systems
#functionalequations #functions #function #maths #counting #sequencesandseries #sequence
via @YouTube @Apple @Desmos @NotabilityApp @googledocs @canva

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

Ferrari's method - method 1
Descartes' method - method 2

bobbyheffley
Автор

Unlike what you seem to think the nested square roots which appear in the solutions of this equation cannot be denested. For example, √(12√2 − 2) cannot be written as √p − √q for any rational p and q because the square of this is (p + q) − 2√(pq). We could take out a factor √2 to get ⁴√2·√(12 − √2) but √(12 − √2) cannot be denested either because 12² − (√2)² = 142 is not the square of a rational number. Also, it is not possible to write √(12√2 − 2) as ⁴√p − ⁴√q for any rational p and q because the square of this is √p + √q − 2·⁴√(pq) meaning that we would need to have pq = 1 and therefore q = 1/p, but there is no rational p such that √p + √(1/p) = 12√2.

Denesting nested square roots used to be a topic in high school algebra and perhaps it still is in countries like India, but in most countries those days seem to be long gone. A century ago any good high school student could denest a denestable square root easily using efficient techniques which were taught _and proved_ in class. But this is no longer the case and as a result such elementary problems now turn up in math Olympiads, which is quite ridiculous. But let's go back in time and discuss and prove a few theorems which were taught and proved in algebra classes.

*Theorem*

If a, b, c, d are positive rational numbers and √b and √d are irrational then a ± √b = c ± √d implies a = c and b = d.

Proof

a ± √b = c ± √d implies ±√b = (c − a) ± √d. Squaring both sides gives b = (c − a)² + d ± 2(c − a)√d and subtracting (c − a)² + d from both sides then gives (b − d) − (c − a)² = ±2(c − a)√d. Now the left hand side is rational, therefore the right hand side must also be rational. But √d is irrational, therefore the right hand side can only be rational if c − a = 0 which implies a = c. With c − a = 0 the equation (b − d) − (c − a)² = ±2(c − a)√d becomes (b − d) − 0 = 0 which implies b = d and this completes the proof.

Next, we have the following

*Theorem*

If a, b, c are positive rational numbers and √c is irrational, then there exist positive rational numbers p and q such that √(a ± b√c) = √p ± √q _if and only if_ a² − b²c is the square of a rational number. If d is a positive rational number such that a² − b²c = d² then p = (a + d)/2 and q = (a − d)/2.

Proof

Let a, b, c be positive rational numbers, √c irrational, and suppose there exist positive rational numbers p and q such that √(a ± b√c) = √p ± √q. Squaring both sides then gives a ± b√c = p + q ± 2·√p·√q or a ± √(b²c) = p + q ± √(4pq). Since √c and therefore √(b²c) is irrational the left hand side is irrational, therefore the right hand side must also be irrational. Since p and q are rational, p + q is rational, consequently √(4pq) must be irrational. In accordance with the previous theorem this implies a = p + q and b²c = 4pq. Consequently, a² − b²c = (p + q)² − 4pq = (p − q)² is the square of a rational number.

Conversely, if a, b, c are positive rational numbers, √c irrational, and a² − b²c is the square of a positive rational number d, then p = ½(a + d) and q = ½(a − d) are positive rational numbers with p > q and such that p + q = a and 4pq = b²c so 2·√p·√q = b√c which implies a ± b√c = p + q ± 2·√p·√q = (√p ± √q)² so √(a ± b√c) = √p ± √q which completes the proof.

In short, if if a, b, c are positive rational numbers, √c irrational, and d is a positive rational number such that d² = a² − b²c then

√(a ± b√c) = √((a + d)/2) ± √((a − d)/2) = ½√(2a + 2d) ± ½√(2a − 2d)

NadiehFan
Автор

Got 'em all (although I went a little further than you did in terms of denesting the solutions)!

scottleung
Автор

but sir i think the answer is not correct as if you put the values of x that you found and put it in the equation there is coming an error of so i think there is no real solution of the sum.

shamicray